Implementasi model EOPACT (Education,Observing,Positif ACTion) terhadap cyberbullying di era digital - Dewi, Seroja Kususma; Rini Diah Puri Handayani; Saputro, Dahvit Danang Adi (IDFoS Indonesia, 2023)
In this modern era, the Internet and social media are increasingly known by the public without realising that they have positive and negative impacts. Cases of cyber bullying often occur on social media which result in losses for both victims and perpetrators. The importance of morals that must be instilled in everyone. As well as the importance of internet restrictions, especially in using social media and education in using social media properly. This research aimed to reduce and handle cyberbullying with the EOPACT Model (education, observation, positive action). With this model, there were many connections between the parties involved, such as in the family, school and in the community. The analytical method used in this research was the Descriptive-Quantitative Method by looking at and analysing current phenomena on social media. There were still many people who made mistakes when using social media. The results of this research showed that there were many factors that caused cyber bullying, as well as applying the EOPACT Model to prevent and understand cyberbullying.